The perceived importance of a leisure education component in outpatient weight management programs serving adult women - Castille, Cheryl L. (My University, 1994)
Previous research has cited the need for new and additional programming for effective long term weight management treatment. This study sought to determine the extent to which health care professionals perceive leisure education as an important component to include in weight management programs serving adult women. 100 health care professionals (physicians, registered dietitians, mental health therapists, exercise physiologists, certified therapeutic recreation specialists) were surveyed regarding important leisure education components to include in weight management programs. Results indicated that all professional groups surveyed believed leisure education was an important component to include. The results of an ANOVA for the components of the leisure education content model were statistically significant for gender. The findings for the other dependent variable, profession, were not significant. The implications of these results for health care providers are discussed.
Keywords: Weight loss - Psychological aspects; Body weight - Regulation; Leisure - Study and teaching; Overweight women - Recreation; Allied health personnel - Attitudes